PMU-PKM DI KELURAHAN BIRING ROMANG KECAMATAN MANGGALA KOTAMADYA MAKASSAR - Asri Usman; Muh. Sobarsyah; Bakhtiar Mustari (Universitas Hasanuddin, 2022)
The results of the initial service team in 2022 the number of UMKM in Biring Romang village Manggala district area ranged from 300 MSMEs from that number of about 50 - 70 UMKM who engaged in mushroom business, of which almost 100% of financial management and management is still very minimal and has not met the standards to be used as a tool to get capital assistance in developing the business it is involved in. This condition is caused because most of the financial managers of UMKM of the highest level of education graduates of The high School (SMA) who have never pursued to the maximum how to manage finances in UMKM that meet the standards. Thus there are 2 problems that are initiated by UMKM actors in Biring Romang village Manggala district of Makassar Municipality, namely HR competence and UMKM financial governance.